Identifikasi Telur Cacing Soil Transmitted Helminthes Pada Tinja Anak di Sekolah Dasar Sijambur Kecamatan Ronggur Nihuta Kabupaten Samosir - Yunita Purba; Aruan, Dyna Grace Romatua (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2023)
Soil Transmitted Helminthes (STH) is a group of intestinal nematodes that can cause infection in humans, either through eggs, larvae or worms which in their life cycle require soil for their maturation process so that there is a change from non-infective to infective stage. Several types of STH that are often found infecting humans include Ascaris lumbricoides, Trichuris trichiura, Hookworm there are two species namely Necator americanus and Ancylostoma duodenale. STH is transmitted by contact with soil contaminated by infected human faeces. The purpose of this study was to determine whether there were STH findings in the feces of children at Sijambur 9 Public Elementary School, Ronggur Nihuta District, Samosir Regency. This type of research was carried out using a qualitative descriptive method using 0.9% physiological NaCl reagent. The results of the study from 54 samples found 7 positive stool samples of STH worm eggs including 2 people with Ascariasis who found worm eggs at codes A34 and A39, and 4 people with Tricuriasis who found worm eggs at codes A07, A08, A23, A29, then there were mixed infection in 1 child with findings of Ascaris lumbricoides and Trichuris trichiura worm eggs at code A18. The conclusion in this study was found 7 samples of stool positive for STH worm eggs from 54 stool samples of children at SD Negeri 9 Sijambur, Ronggur Nihuta District, Samosir Regency with a percentage of 12.9% which is a high result for worm prevalence after treatment. Suggestions for children are expected for children to wash their hands before eating, after defecation and after playing on the ground, get used to wearing footwear when playing or when leaving the house. It is also necessary to regularly take deworming medication to avoid re-infection